The relationship between criminology and criminal law: implications for developing Chinese criminology - Honglan Shuai; Jianhong Liu (Humanities & Social Sciences Communications, 2023)
Abstract During the last four decades, Chinese criminology has grown steadily but modestly. One consensus is the lack of a clear understanding of the relationship between criminology and criminal law. This paper attempts to provide a critical review of the relationship between the two disciplines by first tracing the historical development of criminology in both China and Western countries. It then clarifies the distinctions and overlaps between criminology and criminal law and explains how this relationship has influenced the growth of criminology in China. It concludes by proposing implications for developing criminology in China, particularly discussing potential collaborations that could be forged between criminology and criminal law and how such partnerships can benefit both fields in China.